Scandinavian Multicenter Acute Subdural Hematoma (SMASH) Study: Study Protocol for a Multinational Population-Based Consecutive Cohort. Issue 3 (14th May 2018) - Bartek, Jiri; Laugesen, Christian; Mirza, Sadia; Forsse, Axel; Petersen, Michael Anders; Corell, Alba; Dyhrfort, Philip Wilhelm; Redebrandt, Henrietta Nittby; Reen, Linus; Zolfaghari, Shaian; Tobieson, Lovisa; Carlsvärd, Björn; et al.
Abstract: BACKGROUND: Traumatic acute subdural hematomas (ASDHs) are associated with high rate of morbidity and mortality, especially in elderly individuals. However, recent reports indicate that the morbidity and mortality rates might have improved. OBJECTIVE: To evaluate postoperative (30-d) mortality in younger vs elderly (≥70 yr) patients with ASDH. Comparing younger and elderly patients, the secondary objectives are morbidity patterns of care and 6 mo outcome according to Glasgow outcome scale (GOS). Finally, in patients with traumatic ASDH, we aim to provide prognostic variables. METHODS: This is a large-scale population-based Scandinavian study including all neurosurgical departments in Denmark and Sweden. All adult (≥18 yr) patients surgically treated between 2010 and 2014 for a traumatic ASDH in Denmark and Sweden will be included. Identification at clinicaltrials.gov is NCT03284190. EXPECTED OUTCOMES: We expect to provide data on potential differences between younger vs elderly patients in terms of mortality and morbidity. We hypothesize that elderly patients selected for surgery have a similar pattern of care as compared with younger patients. We will provide functional outcome in terms of GOS at 6 mo in younger vs elderly patients undergoing ASDH evacuation. Finally, clinical useful prognostic factors for favorable (GOS 4-5) vs unfavorable (GOS 1-3) will be identified. DISCUSSION: An improved understanding of the clinical outcome, treatment and resource allocation, clinical course, and the prognostic factors of traumatic ASDH will allow neurosurgeons to make better treatment decisions.